2015
DOI: 10.1177/0020764015612119
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among depression during pregnancy, social support and health locus of control among Iranian pregnant women

Abstract: Clinicians could assess social support and chance HLC to identify and treat women at risk of prenatal depression. By providing support during pregnancy, depression levels in women and its effects on the fetus may be decreased, which could prevent postpartum depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…On the other hand, spouse support among pregnant women was significantly higher compared to non-pregnant subjects. In this regard, the findings of Moshki et (18). Lower perception of social support in pregnant women could occasionally be attributed to the higher sensitivity of women during pregnancy.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, spouse support among pregnant women was significantly higher compared to non-pregnant subjects. In this regard, the findings of Moshki et (18). Lower perception of social support in pregnant women could occasionally be attributed to the higher sensitivity of women during pregnancy.…”
Section: Discussionmentioning
confidence: 92%
“…Possibly the most obvious cause of this difference is the diversity of diagnostic tools used in the studies. For example, in the study of Moshki et al (24), who used EPSS questionnaire to assess depression, 30% depression was reported. Bondad et al (17) estimated the prevalence of depression to be 58% with the Beck questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on health locus of control, prenatal depression based on the EPDS was experienced by 37% of the sample of 208 Iranian pregnant women [6]. Social support and health locus of control were significant predictors of depressive mood in a linear regression model.…”
Section: Risk Factorsmentioning
confidence: 99%